Relations and Relatives. Issue 2 (1st June 2019) - Vilaça, Aparecida
Abstract : This afterword offers a commentary on the concept of relations discussed in the introduction and the individual contributions to this special issue by critically reflecting on the key concepts that have emerged in it. It contributes to the discussion with a reflection on the use of the term parente in Amazonia, showing how its exclusive use in inter-ethnic contexts indicates a play of perspective in the way that relations between different groups of people are experienced.